2004
DOI: 10.1590/s1676-24442004000400007
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos produtos da degradação oxidativa da Hb S nos genótipos SS, SF (S/beta0 talassemia) e AS, em comparação com hemoglobinas normais

Abstract: SF>AS>AA. É importante destacar que as análises indicaram que a simples presença de Hb S no eritrócito, como é o caso do genótipo AS, é capaz de causar elevação da concentração de metemoglobina em 52,62% das amostras analisadas e de induzir a precipitação de corpos de Heinz em 73,68% dos casos estudados. Explicações referentes aos processos oxidativos e redutores das hemoglobinas estudadas são apresentados no texto. Destaca-se, entre os resultados apresentados, a identificação por meio de eletroforese em agaro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It has been shown that hemoglobin has an increased susceptibility to undergo oxidation, and when it is subjected to low oxygen tensions, transforming discoid erythrocytes into sickle erythrocytes, increasing the production of MetHb, hemicromos, or products of heme; and causing globin S precipitation in oxidized form of Heinz bodies (13,15,19) . Naoum e Souza (15) , Allen et al (1) and Silva Filho (19) also observed an increase of MetHb in patients with hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that hemoglobin has an increased susceptibility to undergo oxidation, and when it is subjected to low oxygen tensions, transforming discoid erythrocytes into sickle erythrocytes, increasing the production of MetHb, hemicromos, or products of heme; and causing globin S precipitation in oxidized form of Heinz bodies (13,15,19) . Naoum e Souza (15) , Allen et al (1) and Silva Filho (19) also observed an increase of MetHb in patients with hemoglobinopathies.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma iron content was determined using an atomic absorption spectrophotometer and an air-acetylene flame. ( 15 )…”
Section: Methodsmentioning
confidence: 99%
“…Sickle cell erythrocyte damage is directly intensified by the concentration of intra-erythrocyte Hb S (Beutler et al, 1995;Frenette and Atweh, 2007). Any pathology that increases radical generation, whether by an increase in oxidative stress or by an imbalance of antioxidant defenses, will increase the production of activated oxygen species, and will trigger oxidative processes with free radical generation (Naoum and Souza, 2004). A similar effect was found in cases of iron overload, as a consequence of hereditary hemochromatosis.…”
Section: Introductionmentioning
confidence: 96%